How Implementing the Rights of Wetlands Provides Benefits to People and Wetlands: Relationships, Rights, Responsibilities, Experiences, and Actions - Gillian Davies; Ritesh Kumar; M. Siobhan Fennessy; Nick Davidson; Kai Huschke; Dave Pritchard; Matthew Simpson; Priyanie Amerasinghe; William R. Moomaw; Erin Okuno; Bethanie Walder; Chaturangi Wickramaratne; et al. (Wetlands, 2026)
Rights of wetlands shifts the people-wetlands relationship towards one recognizing the intrinsic rights and living beingness of wetlands, embodying reciprocity, kinship, and gratitude. Recognition of wetland rights occurs within the broader Rights of Nature movement, which has often been led by Indigenous Peoples and local communities from many cultural traditions. Intrinsic wetland rights centre on the right to exist and incorporate seven other rights, forming a holistic framework that enables preservation of wetland ecosystem integrity. These rights provide the basis for a wetland’s thriving existence. The eight rights are: • the right to exist. • their natural place in the landscape; • natural and connected hydrologic regimes; • natural climatic conditions; • naturally occurring biodiversity; • natural ecosystem processes; • natural water, soil, and air quality (i.e., structural integrity and form); and. • regeneration and a naturally determined future. Moral and ethical responsibilities towards these rights include fostering harmonious relationships in and with wetlands, respecting interdependence of all wetland components, safeguarding and fostering conditions enabling rights of wetlands, and acting in a precautionary manner when faced with risks of harm to wetlands. Legal and policy responsibilities include acknowledging plural worldviews, recognising legal standing and political orientations to represent and defend wetland rights, providing adequate means for wetland representation and defending and advocating for wetlands, and using best available science to restore degraded wetlands and support regeneration, thereby supporting harmonious societal relationships with wetlands. Opportunities for implementation of rights of wetlands at a variety of scales (individual, community, national, and global) are explored, and training/guidance resources are referenced.